(untitled) (Journal of Partial Differential Equations, 2003)
" In this paper, we prove that in the inviscid limit the solution of the generalized derivative Ginzburg-Landau equations converges to the solution of derivative nonlinear Schr00f6dinger equation, we also give the convergence rates for the difference of the solution."